PELATIHAN STRATEGI GROUP INVESTIGATION (GI) MENGGUNAKAN MEDIA E-COOLE (E-COOPERATIVE LEARNING) PADA GURU MGMP BAHASA INGGRIS SMP KABUPATEN PEKALONGAN - Ida Ayu Panuntun; Rizka Hayati; Erwan Kustriyono (LPPM Universitas Pekalongan, 2021)
Pedagogy competence is the main competence that must be owned by educators. Moreover, mastering science and technology are also important for educator to support the pedagogical competence. Based on the result of situation analysis, the data showed that the teaching learning model used by junior high school English teacher in Pekalongan regency was Teacher centered leaning (TCL). Moreover, it was implemented without adequate technological support. Thus, that kind of learning pattern seemed monotonous and can reduce students’ interest in learning English. The solutions for the problems were : (a) applying cooperative method in learning (b) offering E-Coole (E-Cooperative learning) which is a web-based combination of cooperative learning and E-learning, the application focused on group Investigastion (GI). The stages in this PKM was carried out though several series, those were : (a) socialization, it was intended to introduce and explain PKM program to PKM partner. (b). training to provide definitions and basic concept of E-Coole. (C) mentoring teachers’ activities it was intended to implement E-Coole for grup Investigation, (d) evaluation to measure the abitily of teachers in using E-coole application with grup investigation strategy. The result of this PKM in this article included : (a) an understanding of PKM activities organized by PKM team and subject of PKM, namely the English MGMP Junior High school in Pekalongan regency, (b) PKM participants understood the definitions and basic concept of E-Coole, (c) the mentoring activities run smoothly in schools with a focus on group investigation strategies (d) there was an increase in the ability of teachers to master and use E-Coole application with Group Investigation strategy. Key words : E-Coole, training and mentoring, Group Investigation strategy